DNA-encoded focused indazole library synthesis by a palladium-mediated CN(sp2) cross-coupling reaction between DNA-linked (hetero)aryl halides and aromatic nitrogen heterocycles. (27th April 2022) - Yang, Juan; Xia, Shengdi; Liu, Jiaxiang; Yu, Zikun; Mei, Lianghe; Lu, Weiwei; Chen, Yulin; Chen, Shaopeng; Wang, Xuan; Lu, Xiaojie
Graphical abstract: Abstract: Incorporating various heteroaryl motifs into small-molecule moieties of DNA-encoded libraries is beneficial to support hit identification. More privileged heterocycles based libraries are urgently needed to expand the chemical space of the DNA encoded library. Because currently published on-DNA CN cross-coupling methods mainly focused on exocyclic aromatic amines, lacking systematic investigation for incorporating pharmaceutically valuable N -aryl hetero-aromatic moiety into DNA-encoded libraries, in this paper, we have reported an on-DNA protocol to attach the DNA-linked electrophiles to the (H) N -heteroaryl rings. This method could translate the monofunctional heteroaryl agents into "bifunctional building blocks", which have been applied for the DNA encoded focused indazole library synthesis.